3- The Intellectual Dimensions of Corruption in Nigeria - Omotola, J. Shola (African Sociological Review, 2023)
Against the background of the deepening crisis of the Nigerian academy, this paper undertakes a critical analysis of the intellectual dimensions of corruption in Nigeria. It argues that the incorporation of the academy, particularly its intellectual components, into the ‘corruption enterprise’ has impacted on corruption discourses and analyses – most notably the polarisation into two realms, the public and the private. This characterisation represents in itself a distinct dimension of intellectual corruption, apart from its other forms as analysed in the paper. This development has had negative implications for both state and society, particularly on their democratisation and developmental drives through the reversal and perversion of routinised academic culture of quality teaching, research and publication. Unless critical measures are taken to sanitise the Nigerian academy within a broader framework of a reformist state, the crisis of the academy being a reflection of the deepening crisis of the state, the paper submits that corruption analysis and their outcomes may not advance the anti-corruption crusade of government.